Reduction of Diagnostic Window by New Fourth-Generation Human Immunodeficiency Virus Screening Assays - Weber, Bernard (American Society for Microbiology, 1998)
In order to reduce the diagnostic window between the time of human immunodeficiency virus (HIV) infection and laboratory diagnosis, new screening enzyme-linked immunosorbent assays (ELISAs) which permit the simultaneous detection of HIV antigen and antibody have been developed. Two fourth-generation assays, HIV DUO (Biomérieux) and HIV Combi (Boehringer Mannheim), for the combined detection of HIV antigen and antibody, were compared with a third-generation assay (HIV-1/HIV-2 3rd Generation Plus enzyme immunoassay [EIA]; Abbott) and a p24 antigen test (HIV-1 Ag monoclonal; Abbott). A total of 17 seroconversion panels, 15 cell culture supernatants infected with different HIV type 1 (HIV-1) subtypes, and 255 potentially cross-reactive serum samples were tested. Ten seroconversions were detected an average of 8.1 days earlier with HIV DUO and 7.5 days earlier with HIV Combi than with the third-generation ELISA. Overall, in the 17 seroconversion panels tested, HIV DUO detected HIV-1 infection an average of 4.8 days and HIV Combi detected infection an average of 4.4 days earlier than HIV-1/HIV-2 3rd Generation Plus EIA. HIV antigen was detected with HIV DUO and HIV Combi in all of the 15 cell culture supernatants infected with different HIV-1 subtypes, including subtype O. With fourth-generation assays, considerably fewer false-positive results (n = 4 to 6) were obtained, in comparison with the third-generation EIA (n = 18). Fourth-generation assays permit an earlier diagnosis of HIV infection than third-generation antibody screening assays through the detection of p24 antigen, which may be present in serum samples from individuals with recent HIV infection prior to seroconversion.